2021
DOI: 10.14802/jmd.21034
|View full text |Cite
|
Sign up to set email alerts
|

Management of Parkinson’s Disease in the COVID-19 Pandemic and Future Perspectives in the Era of Vaccination

Abstract: The current coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARSCoV- 2) has led to a serious global health crisis. Increasing evidence suggests that elderly individuals with underlying chronic diseases, including Parkinson’s disease (PD), are particularly vulnerable to this infection. Changes in the routine care of PD patients should be implemented carefully without affecting the quality provided. The utilization of telemedicine for clinical consultation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…The effect of COVID-19 on PD, the heart, and the brain is still unknown due to the limited literature, especially since we know that the lungs are badly affected by COVID-19 [ 54 , 55 ]. Note that PD patients already have several other comorbidities due to the older age group [ 6 , 16 , 56 ]. The symptoms related to PD with COVID-19 and other comorbidities introduce nonlinearity, causing challenges in the ML system for CVD/stroke risk stratification [ 16 ].…”
Section: Pathophysiology Of Lung and Parkinson’s Disease During Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of COVID-19 on PD, the heart, and the brain is still unknown due to the limited literature, especially since we know that the lungs are badly affected by COVID-19 [ 54 , 55 ]. Note that PD patients already have several other comorbidities due to the older age group [ 6 , 16 , 56 ]. The symptoms related to PD with COVID-19 and other comorbidities introduce nonlinearity, causing challenges in the ML system for CVD/stroke risk stratification [ 16 ].…”
Section: Pathophysiology Of Lung and Parkinson’s Disease During Covid-19mentioning
confidence: 99%
“…During the period of lockdown, less importance was given to PD-affected patients, leading to heart attack and stroke in PD patients [ 16 ]. The connection between cardiovascular disease (CVD), stroke, and PD with COVID-19 seems particularly important due to several observations.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review found that proactively educating PWP regarding COVID-19 infection prevention should be undertaken [52 ▪ ]. Education could include reviewing effective strategies, such as hand washing, current public health guidelines, providing advice for lockdown preparedness and the importance of early vaccination [53,54]. Another education activity could include advance care planning, which can be conducted on virtual platforms.…”
Section: Impact Of Telemedicine On Movement Disorder Carementioning
confidence: 99%
“…Increasing evidence suggests that PwP are particularly vulnerable to the sequelae of SARS-CoV-2 infection due to intrinsic features of PD, including, but not limited to, rigidity of respiratory muscles, abnormal posture and impaired cough reflex ( Lau, Lau, & Ibrahim, 2021 ; van Wamelen et al, 2020 ), while they are likely to experience an aggravation of their motor and non-motor symptoms, especially in cases of advanced PD ( Merello, Bhatia, & Obeso, 2021 ). Restrictions of mobility, often accompanying PD, limited access to healthcare resources, and reduced social interactions due to the imposed lockdown regulations might further deteriorate patients’ health and quality of life.…”
Section: Covid-19 Vaccinationsmentioning
confidence: 99%
“…Vaccination against SARS-CoV-2 should be a priority in the management of PwP during the pandemic ( Lau et al, 2021 ). The MDS has released a Covid-19 vaccine statement to address aspects of Covid-19 vaccination among PwP ( Bloem et al, 2021 ).…”
Section: Covid-19 Vaccinationsmentioning
confidence: 99%